Seni Tradisional Hadra Pada Lampung Saibatin - Septa Dewi; Risma Margaretha Sinaga; Henry Susanto (Journal of Social Science Education, 2021)
Abstract:Hadra Traditional Art in Lampung Saibatin. The research objective was to determine the meaning of Hadra Traditional Art. The method used is hermeneutic. Based on the results of research on the art of hadra, the elements are song, wasp and dance. The meaning of the traditional art of hadra: an expression of praise for the exemplary nature of Allah SWT and the longing for the presence of the Prophet Muhammad, advice on harm and teachings to make the Qur'an a guide to life, a form of expression of pleasure in order to get closer to the creator, teachings to live with mutual respect and manners. Keywords:Hadra, Meaning and Lampung Saibatin